A novel PSMA/GCPII-deficient mouse model shows enlarged seminal vesicles upon aging - Vorlová, Barbora; Sedlák, František; Kašpárek, Petr; Šrámková, Karolína; Malý, Marek; Zámečník, Josef; Šácha, Pavel; Konvalinka, Jan (The Prostate, 2019)
BACKGROUND: Prostate-specific membrane antigen (PSMA), also known as glutamate carboxypeptidase II (GCPII), is an important diagnostic and therapeutic target in prostate cancer. PSMA/GCPII is also expressed in many healthy tissues, but its function has only been established in the brain and small intestine. Several research groups have attempted to produce PSMA/GCPII-deficient mice to study the physiological role of PSMA/GCPII in detail. The outcomes of these studies differ dramatically, ranging from embryonic lethality to production of viable PSMA/GCPII-deficient mice without any obvious phenotype. METHODS: We produced PSMA/GCPII-deficient mice (hereafter also referred as Folh1-/- mice) by TALEN-mediated mutagenesis on a C57BL/6NCrl background. Using Western blot and an enzyme activity assay, we confirmed the absence of PSMA/GCPII in our Folh1-/- mice. We performed anatomical and histopathological examination of selected tissues with a focus on urogenital system. We also examined the PSMA/GCPII expression profile within the mouse urogenital system using an enzyme activity assay and confirmed the presence of PSMA/GCPII in selected tissues by immunohistochemistry. RESULTS: Our Folh1-/- mice are viable, breed normally, and do not show any obvious phenotype. Nevertheless, aged Folh1-/- mice of 69-72 weeks exhibit seminal vesicle dilation, which is caused by accumulation of luminal fluid. This phenotype was also observed in Folh1+/- mice; the overall difference between our three cohorts (Folh1-/- , Folh1+/- , and Folh1+/+ ) was highly significant (P < 0.002). Of all studied tissues of the mouse urogenital system, only the epididymis appeared to have a physiologically relevant level of PSMA/GCPII expression. Additional experiments demonstrated that PSMA/GCPII is also present in the human epididymis. CONCLUSIONS: In this study, we provide the first evidence characterizing the reproductive tissue phenotype of PSMA/GCPII-deficient mice. These findings will help lay the groundwork for future studies to reveal PSMA/GCPII function in human reproduction.
Keywords: prostate-specific membrane antigen; knockout mice; semenné váčky; dilated seminal vesicles; Humans; Seminal Vesicles; glutamátkarboxypeptidasa II; Antigens, Surface; stárnutí; antigeny povrchové; lidé; zvířata; Immunohistochemistry; myši; Aging; myši inbrední C57BL; imunohistochemie; Membrane Glycoproteins; membránové glykoproteiny; Mice; Male; Mice, Inbred C57BL; glutamate carboxypeptidase II; Glutamate Carboxypeptidase II; Animals; mužské pohlaví; Folh1